Supplementation of beef cattle grazing Brachiariabrizantha during the dry and rainy seasons: performance and carcass ultrasound prediction - Guerra, Geisi Loures; Mizubuti, Ivone Yurika; Ribeiro, Edson Luis de Azambuja; Prado-Calixto, Odimári Pricila; Silva, Leandro das Dores Ferreira da; Pereira, Elzânia Sales; Massaro Junior, Fernando Luiz; Guerra, Antonio Loures; Fernandes Júnior, Francisco; Henz, Éderson Luis (Semina: Ciências Agrárias, 2016)
The aim of this study was to evaluate the influence of genetic group, sex and level of protein-energy supplementation on the performance and carcass traitsultrasound prediction of weaned calves Nellore and crossbred animals ½ Nellore x ½ Aberdeen Angus. A completely randomized design in a factorial 2x2x2, were used, with two levels of protein-energy supplementation, two sex and two genetic groups. Fifty-six animals were used (28 Nellore and 28 crossbred ½ Nellore x ½ Aberdeen Angus), equally divided between males and females, maintained on grazing Brachiariabrizanthacv. Marandu and evaluated in three experimental periods: period 1 = protein-energy supplementation in the dry season; period 2 = protein-energy supplementation during the rainy season; period 3 = only mineral supplementation. In the dry season, they were supplemented with levels of 0.5 and 1% of body weight (BW) and in the rainy season with 0 and 1% BW. Dry matter intake (kg day-1, % BW, g kgBW0.75-1) was estimated. In vivo ultrasound measurements of carcass were: loin eye area (LEA), fat thickness (FT) and rump fat thickness (RFT). There was influence of genetic group and protein-energy supplementation levels on average daily gain (ADG) of animals in period 1 and 2 (P < 0.05). Sex affected the ADG only in period 2, and the males had 754 gday-1 and females, 582 g day-1. There was no interaction of genetic group x sex x supplementation level. At the end of the experimental period (end of period 3), it was found that male animals and crossbred animals ½ Nellore x ½ Aberdeen Angus had higher ADG (716 and 748 g day-1, respectively). The values of dry matter intake (DMI) were influenced by genetic group and sex, in all periods, verifying highest intake in crossbred animals ½ Nellore x ½ Aberdeen Angus, with better feed conversion for crossbred animals. Regarding ultrasound measurements taken on the carcass, the influence of sex on FT and RFT, it was observed, and the males showed higher values, 3.24 and 4.62 mm, respectively. LEA was influenced by protein-energy supplementation levels in the second period, herein animals receiving 1% of BW, showed higher values (56.04 cm2) than those receiving 0.5% of BW supplement (48.38 cm2). The use of protein-energy supplementation with 0.5% of BW in the dry season and 1% of BW in the rainy season, the best results of performance and contributes to larger loin eye area.